The Future of New Zealand’s Cities as Forecast by the Literary Method of Urban Design - Marshall, Alan (วารสารศิลปะและวัฒนธรรมลุ่มแม่น้ำมูล, 2025)
An exploration of a novel design method (called the Literary Method of Urban Design) is attempted and applied to three New Zealand cities. This Literary Method uses local or national literary works as a lens to forecast urban futures. Working with this Method, this paper interprets the city of Christchurch through Samuel Butler’s 19th century novel Erewhon, the city of Napier through Herbert Guthrie-Smith’s ecological book Tutira, and the city of Auckland through John Mulgan’s interwar novel Man Alone. These case studies highlight how literature can inform urban sustainability, offering insights into technological progress and restraint, environmental adaptation, and communal resilience. The findings suggest, generally, that literature – as both art and foresight – provides a powerful tool for reimagining cities in response to 21st century challenges. In this paper, specifically, the findings indicate that New Zealand futures may well be prosperous in some cases, but also catastrophic in others. Even in the catastrophic cases, though, the literary texts explored can offer a pathway to urban survivability.